Policies to encourage the preservation of cultural heritage: the mineiro example - Clark, Giovani; Felizalle Guimarães, Patrícia (Revista da Faculdade de Direito do Sul de Minas, 2019)
Culture, an important driver of the human, economic and sustainable development of any region, is linked to the Constitutional Economic Order that imposes development and dignified existence − article 170 of the Federal Constitution of 1988. This article analyzes, through literature review, the appreciation of the cultural heritage of our Nation and specifically examines the paradigm of the State of Minas Gerais in the municipalization of protective policies of its cultural heritage. Minas Gerais has excelled in its successful experience of creating revenue of financial and fiscal incentives to safeguard cultural heritage through a program that enables the participation of private and public entities, including citizens aware of the need to preserve and revitalize Minas Gerais cultural heritage.